How can I find the momentum squared operator?

In summary, the conversation discusses the momentum squared operator and its derivation. The conversation also mentions an attempt to derive the momentum squared operator using similar methods, but it results in an imaginary answer.
  • #1
Harrisonized
208
0

Homework Statement



This problem is about the momentum squared operator. First, I state how I saw the derivation for the momentum operator. Then I state how I attempt to (and fail to) derive the momentum squared operator using the same methods.

Homework Equations



<p> = ∫ ψ*(ħ/i ∂/∂x)ψ dx

The construction for this definition is straightforward. We start with the fact that

<p> = m d/dt <x>
= m ∂/∂t ∫ ψ* x ψ dx
= m ∫ x ∂/∂t ψ*ψ dx
= m ∫ x ∂/∂x [iħ/2m ψ*(∂ψ/∂x)-(∂ψ*/∂x)ψ] dx (from the probability flux)

Here, we use the substitution x(∂/∂x)f(x) = ∂/∂x[xf(x)]-f(x) and say that since square integrable functions (that is, normalizable functions) must have derivatives that vanish, the first part is zero. We're left with "-f(x)", which is:

= m(iħ/2m) ∫ -[ψ*(∂ψ/∂x)-(∂ψ*/∂x)ψ] dx
= ħi/2 ∫ [(∂ψ*/∂x)ψ-ψ*(∂ψ/∂x)] dx
= ħi/2 ∫ (∂/∂x)ψ*ψ -2ψ*(∂ψ/∂x) dx

Again, the derivative vanishes.

= ħ/i ∫ ψ*(∂ψ/∂x) dx

Hence, we define the momentum operator as:

p = ħ/i (∂/∂x)

The Attempt at a Solution



To obtain the momentum squared, I go through the following steps (the first few steps are about the same):

<p> = m2 d/dt <x2>
= m2 ∂/∂t ∫ ψ* x2 ψ dx
= m2 ∫ x2 ∂/∂t ψ*ψ dx
= m2 ∫ x2 ∂/∂x [iħ/2m ψ*(∂ψ/∂x)-(∂ψ*/∂x)ψ] dx (from the probability flux)

From here, I use:

x2(∂/∂x)f(x) = ∂/∂x[x2f(x)]-2xf(x) (1)

The first part vanishes. We're left with 2xf(x)

= m2(iħ/2m) ∫ 2x [ψ*(∂ψ/∂x)-(∂ψ*/∂x)ψ] dx
= mħi ∫ x [ψ*(∂ψ/∂x)-(∂ψ*/∂x)ψ] dx
= mħi ∫ x [(∂/∂x)[ψ*ψ]-2(∂ψ*/∂x)ψ] dx

using another x(∂/∂x)f(x) = ∂/∂x[xf(x)]-f(x) type substitution:

= mħi ∫ -[ψ*ψ]-2x(∂ψ*/∂x)ψ] dx
= -mħi (1+∫ 2x(∂ψ*/∂x)ψ] dx)

It's obviously wrong since it's imaginary. Going back to step (1), which I bolded, and making the substitution

x(∂/∂x)g(x) = ∂/∂x[xg(x)]-g(x), where g(x) = (∂/∂x)g(x)=f(x), I'm left with 2g(x)=2∫f(x)dx

= 2mħi ∫∫ [(∂/∂x)[ψ*ψ]-2(∂ψ*/∂x)ψ] dx2

I don't understand why this happens. I get an imaginary answer every time. :(
 
Last edited:
Physics news on Phys.org
  • #2
your equation <p2> = m2 d/dt <x2> is wrong
 
Back
Top